Biology of Diaphorina citri (Hemiptera: Liviidae) under glass house conditions in Palmira, Colombia - García, Yesenia; Patricia Ramos, Yaneth; Sotelo, Paola Andrea; Kondo, Takumasa (Revista Colombiana de Entomología, 2016)
In this study, the morphological characteristics of each stage of development, duration, survival, ecological parameters, reproductive capacity, longevity of adults, and stage-specific mortality of Diaphorina citri (Hemiptera: Liviidae) were determined. It was conducted in a greenhouse (maximum temperature: 37.1 ± 5.1 °C, minimum temperature: 25.0 ± 2.0 °C; maximum relative humidity: 67.0 ± 6.2%, minimum relative humidity: 39.5 ± 10.9%; 12: 12 h Light: Dark, natural light conditions) in the municipality of Palmira, Valle del Cauca. Mean time from egg to adult was 15.41 ± 0.49 days. The median survival time for females was 48.25 days and 50 days for males. The survival rate to adult stage of D. citri was 6.86% with the highest mortality rate recorded for first-instar nymphs (81%). Females oviposited an average of 237 eggs during their reproductive cycle. A dichotomous key, an essential tool for conducting biological studies, is provided to separate the different growth stages of the Asian citrus psillid. Studies on the biology of D. citri will serve as a baseline for the mass rearing of its parasitoid, T. radiata.